Finding the Characteristics of Creative People in Developing Villages for the Foundation of Creative Industry - Herlina Herlina; Budi Teguh Harianto (Universitas Muhammadiyah Ponorogo, 2021)
Every element of the community in the village should participate to optimize the potency that the village has. The village in Kuala Betara sub-district have marine resources, agriculture and plantation. Even with all of that benefit, if there is no support from creative human resources, it must be difficult for the village to create creative industry. Small and medium industry entrepreneurs have been utilizing the natural wealth of the village as the raw material of their production but they face obstacles in managing it due to their limited skills that are acquired self-taught and passed on from generation to generation, limited capital, unsophisticated production and packaging tools, limited market access due to limited production and the market is conventional only, including being not optimal in involving youth who are better in information technology. Meanwhile, the information about creative products can be easily obtained through internet. In addition, the youth also have not optimized the usage of internet as the media to collect creative ideas that will be useful in developing products of small and medium industry in the village. Besides, this industry can be a platform for youth to increase the quality through creativity. The method used in this research is survey with descriptive analysis. The result shows that the creativity of small and medium industry entrepreneurs and youth is in average level. Started from the main characteristics of creative people, possible characteristic of creative people, and side characteristic of creative people. . Even so, it is found that there are three entrepreneurs of small and medium industry and 42 youth who are belong to high level of creative people. These kind of people are the main and valuable assets to collaborate and becoming the foundation of creative industry in village.